Relationship between prospective memory and executive functions in predicting symptoms of anxiety and depression in students - Ahsant, Negar; Khosravi, Zohreh (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the present research was to investigate the relationship between prospective memory and executive functions in predicting symptoms of anxiety and depression in students. Our research was applied and methodologically a descriptive correlational design. The present statistical population included all students studying in the academic year of 2013-2014 in Shiraz University; using a simple random method, we selected 250 of them as a sample. Tools used included retrospective and prospective memory questionnaires, the Wisconsin card (Problem Solving) Card sorting Test, the Continuous Performance Test (CPT), the test of Tower of London and the Depression, Anxiety, and Stress Scale (DASS-21). We used Pearson correlation coefficient and regression for the investigation. The results showed that prospective memory has a significant negative correlation with depression and anxiety at the level of 0.01. Prospective memory also explained 0.30 percent of anxiety variance and 0.43 percent of depression variance. In addition, there is a significant negative relationship between depression and executive functions of planning and the number of classes at the level of 0.01 and a significant positive relationship between depression and executive function of perseveration error at the level of 0.01. The executive function of perseveration can predict and explain 0.27% of anxiety variance and 0.43% of depression variance.